Address before the Overseas Press Club of America, New York City, March 16, 1948 - McCloy, John, J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, discussed the appropriate function of the Bank. It cannot be the overall financer of global balance of payment deficits. It can finance economically strategic and productive projects. It can be the bridge between government and private financing, and thereby complement the Marshall Plan. He discussed administration of the Marshall Plan and national self-interest. The opportunity afforded by recovery of Europe and its closer integration remains the first and most promising objective to achieve.